Preoperative imaging for endometriosis awareness: an online survey study - Bassem Gerges; Allie Eathorne; George Condous (Frontiers in Reproductive Health, 2026)
Introduction In 2024, an international consensus statement on non-invasive imaging techniques for the diagnosis of pelvic deep endometriosis was published, recommending transvaginal sonography as the first-line imaging modality because of cost, availability, and low impact on the environment. Despite the increasing body of evidence supporting the use of imaging in the preoperative diagnosis of endometriosis, there is a paucity of data to confirm patient awareness. The aim of this study was to use an online survey or questionnaire from patients to collect quantitative data regarding their awareness, exposure, and experience with preoperative imaging for the diagnosis of endometriosis. Methods This was a cross-sectional study, based on an online, international survey completed by patients with self-reported endometriosis from multiple online endometriosis groups. The survey went live from November 2025 to March 2026 and consisted of women and gender-diverse individuals with self-reported endometriosis, with a minimum required number of 100 participants. Results A total of 180 participants started the survey, of which 142 (78.9%) completed the exercise. The mean age of the participants was 31.6 [standard deviation (SD) 8.7] years, with a median time of endometriosis diagnosis of 2 years (interquartile range 1–5), of whom 99 (69.7%) had at least one surgery, with a mean number of surgeries of 1.8 (SD 1.2). The majority of participants were from Australia (66.2%), followed by Canada (16.9%), New Zealand (11.3%), and the United Kingdom (2.1%), and an equal number were from Brazil, India, the Philippines, and Spain (0.7% each). Overall, 53.5% of participants agreed that endometriosis can be diagnosed without surgery, while only 32.4% agreed that bowel endometriosis can be diagnosed before surgery. Of these, the percentages of participants who agreed that bowel endometriosis can be preoperatively diagnosed with ultrasound, magnetic resonance imaging, computed tomography, and colonoscopy were 32%, 35%, 15%, and 15%, respectively. The participants obtained knowledge about endometriosis investigations and treatments from various sources, including their gynecologists (71.8%), general practitioners (57%), fertility specialists (11.3%), family members (12%), friends (21.8%), social media (68.3%), and other sources (29.6%). Conclusion There is a disparity between participant awareness in our study and the evidence in the literature regarding the availability and accuracy of preoperative imaging for the diagnosis of deep endometriosis, possibly due to the misinformation disseminated via social media .